Latin American and European regional integration in the 21st century: framework for reflection on its present and future (2020)
This book covers a series of investigations that promote reflections on two themes in general: the framework of regional integration in the 21st century and the present and future situations of Latin American and European integration. The topics analyzed in the first part include a wide range of nuances regarding the regional integration process, both from the perspective of your current situation and from proposals that aim to channel your future. The analysis of the characteristics and implications of free trade agreements highlights the existence of ideological positions, which hinder the academic debate on regional integration and the same integration process since that time and efforts could be better used to analyze, reflect and build viable proposals and recommendations. In the second part, we find a historical, current and prospective review of the relations be-tween Mercosur and the European Union. Both the general framework of the first section and the specific situations of the second show the richness and variety of interpretations currently produced on regional integration. We consider the participation of academics from different fields, disciplines and different national experiences to be positive. To those of Argentina, Brazil, El Salvador, Mexico, Uruguay and Venezuela, two of the EU are added, while in the disciplines they represent we find political science, economics, history, international relations, and sociology.